Aberrant distribution and function of plasmacytoid dendritic cells in patients with ankylosing spondylitis are associated with unfolded protein response. Issue 6 (21st January 2020) - Liu, Chin‐Hsiu; Chou, Chung‐Tei; Chen, Chen‐Hung; Chen, Chun‐Hsiung; Yang, Shii‐Yi; Ko, Yi‐An; Wu, Yi‐Ting; Wang, Chih‐Chien; Liu, Feng‐Cheng; Yue, Chung‐Tai; Hung, Shih‐Chieh; Tzeng, I‐Shiang; et al.
Abstract: Although human leucocyte antigen (HLA)‐B27 is strongly associated with ankylosing spondylitis (AS), the association of unfolded protein response (UPR) induced by HLA‐B27 misfolding in AS remains controversial. Since dendritic cells (DCs) are crucial in induction of AS in HLA‐B27‐transgenic rats, and plasmacytoid DCs (pDCs) belong to one type of DCs, we here aim to study the relevance of pDCs and UPR in AS. Peripheral pDCs were isolated from 27 HLA‐B27(+) AS patients and 37 controls. The bone marrow (BM) and synovium of inflamed hips from AS patients and controls were obtained. We found a significantly higher frequency of pDCs in the peripheral blood, BM, or inflamed synovium of hips, which is associated with the enhanced expression of pDC trafficking molecules, CCR6 and CCL20 in the synovium of AS patients. Functional analysis further revealed that several inflammatory cytokines, including TNFα, IL‐6, and IL‐23, secreted by pDCs were significantly increased in AS patients as compared with those in controls. Remarkably, protein kinase RNA‐like endoplasmic reticulum kinase (PERK) pathway in UPR was up‐regulated in pDCs of AS patients. Notably, PERK inhibitor treatment significantly inhibited the enhanced cytokine production by pDCs of AS patients. Further, the extent of PERK activation was significantly associated with the increased disease severity of AS patients. Our data uncover the aberrant distribution and function of pDCs in AS patients. The up‐regulated PERK pathway in UPR of pDCs not only contributes to enhanced cytokine production of pDCs, but also is associated with increased disease activity of AS patients.